2022
DOI: 10.1155/2022/2434938
|View full text |Cite
|
Sign up to set email alerts
|

LINC01140 Targeting miR-452-5p/RGS2 Pathway to Attenuate Breast Cancer Tumorigenesis

Abstract: Background. LINC01140 has been known to be involved in various cancers. However, its underlying molecular mechanism in breast cancer (BC) needs further exploration. Methods. The LINC01140, miR-452-5p, and RGS2 levels in BC cells and tissues were evaluated by means of RT-qPCR and western blotting. The variations in the biological functions of BC cells were analyzed through CCK-8, transwell, western blotting, and xenograft experiments to observe cell viability, migration, levels of apoptosis-related proteins (Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…At present, none of the new blood markers for the diagnosis of breast cancer, such as circulating tumor cells (17) and microRNA (18,19), has reached the standard of clinical routine practice, while circulating immune cells are considered a potential key breakthrough. This study found that the proportion of CD4 + Tn cells was decreased in patients with breast cancer, while the absolute number and proportion of CD4 + CD57 + T and CD4 + PD-1 + T cells were significantly increased compared with those in patients with benign tumors.…”
Section: Discussionmentioning
confidence: 99%
“…At present, none of the new blood markers for the diagnosis of breast cancer, such as circulating tumor cells (17) and microRNA (18,19), has reached the standard of clinical routine practice, while circulating immune cells are considered a potential key breakthrough. This study found that the proportion of CD4 + Tn cells was decreased in patients with breast cancer, while the absolute number and proportion of CD4 + CD57 + T and CD4 + PD-1 + T cells were significantly increased compared with those in patients with benign tumors.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Li investigated the role of microRNAs (miRNAs) in breast cancer, specifically focusing on miR-452-5p. They found this miRNA to be upregulated in breast cancer tissues, suggesting it plays a role in tumor development [30]. Building on the understanding of miR-452-5p's anti-apoptotic role in colorectal cancer, this study by Lin et al delves deeper into the complex mechanisms by which miRNAs regulate apoptosis.…”
Section: Cerna Network and Apoptosismentioning
confidence: 91%
“…MicroRNA (miRNA) is a kind of cellular endogenous non-coding RNA molecule with the function of regulating the translation of protein, which is about 22 nucleotides long 10 , 11 . It was reported that miR-452-5p exerted different effects in different types of tumors 12 , 13 . The regulatory role of miR-452-5p in NSCLC remains unclear, and if miR-452-5p could affect the EMT process of NSCLC cells has not been reported.…”
Section: Introductionmentioning
confidence: 99%